The impact of marine safety in improving the management of marine vessels (Journal of Namibian Studies : History Politics Culture, 2023)
The aims of current article to activate the maritime safety culture of the Iraqi Oil Tanker Company's naval crews, which is reflected in improving the work of offshore vessels and increasing their operational efficiency, as well as preventing the occurrence of risks through prior assessment of maritime accidents. The researcher distributed the checklist to diagnose the problem for the article survey, and to achieve the research objectives, the researcher prepared the hypothetical chart showing the kind of the association between the primary factors reflected in the dependent variable (maritime management) and the independent variable (maritime safety), and where the study population consist of (300) people and the sample contained (169) people. The sample, which consists of people who work on marine vessels owned by the Iraqi Oil Tanker Company, received the questionnaire. In order to analyze the data, the researcher used statistical software (EXCEL V.10, SPSS.V.23).The main hypothesis, which seeks to understand the relationship of correlation and impact among the dependent variable (management of marine vessels) and the independent variable (maritime safety) , in addition to identify the flaws which jeopardize the safety of Iraqi marine vessels owned by the Iraqi Oil Tanker Company, was accepted based on the research's findings.